2018
DOI: 10.1016/j.jdent.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of external and internal implant-abutment connections for implant supported prostheses. A systematic review and meta-analysis

Abstract: Internal connection implants should be preferred over external connection implants, especially when different risk factors that may contribute to increased marginal bone loss are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 57 publications
3
62
2
5
Order By: Relevance
“…The hybrid surface has the advantage of being moderately rough along the implant body, which promotes osseointegration 24 and minimally rough around the implant neck, which is suggested to be less susceptible to develop peri-implantitis on the long term, especially in high-risk patients. 17 [26][27][28] In the present study, one patient showed extensive crestal bone loss beyond the normal bone remodeling, at both the MSC (1.75 mm) and DCC implant (3.93 mm), 3 months post-implant placement. In the present study, no difference in initial crestal bone loss was found between the MSC and the DCC implant after a follow-up of at least 1 year.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The hybrid surface has the advantage of being moderately rough along the implant body, which promotes osseointegration 24 and minimally rough around the implant neck, which is suggested to be less susceptible to develop peri-implantitis on the long term, especially in high-risk patients. 17 [26][27][28] In the present study, one patient showed extensive crestal bone loss beyond the normal bone remodeling, at both the MSC (1.75 mm) and DCC implant (3.93 mm), 3 months post-implant placement. In the present study, no difference in initial crestal bone loss was found between the MSC and the DCC implant after a follow-up of at least 1 year.…”
Section: Discussionmentioning
confidence: 45%
“…This outcome confirms a previous paper by Spinato and colleagues. 17 [26][27][28] In the present study, one patient showed extensive crestal bone loss beyond the normal bone remodeling, at both the MSC (1.75 mm) and DCC implant (3.93 mm), 3 months post-implant placement. Bone…”
Section: Discussionmentioning
confidence: 45%
“…11,12 However, the findings of the present systematic review should be analysed with caution due to the small number of randomized clinical trials included, which can be considered a limitation. In addition, other factors such as number/position, 14 connection type, 42 length/diameter of the implant, 43,44 loading protocol 45 and follow-up period 1 are considered as influencing factors; unfortunately, sub-analyses could not be performed to verify the influence of these variables in association with the attachment system. Further randomized clinical trials are needed to evaluate these factors in patients with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…4 Thus, marginal bone stability is considered one of the most important issues in implant dentistry. [11][12][13][14] Additionally, occlusal overload is considered to be associated with periimplant bone resorption. 9,10 The associations between various factors such as systemic diseases, implant position, prosthetic design, implant connection types, and marginal bone resorption are also being examined.…”
mentioning
confidence: 99%